Association between insufficient venous systems and clinical manifestations in chronic venous disease of the lower limbs: Asociación entre sistemas venosos insuficientes y manifestaciones clínicas en enfermedad venosa crónica de miembros inferiores - Mendoza Rojas, Hubert James (2024)
Introduction: The clinical, etiological, anatomical and pathophysiological classification (CEAP) standardizes the manifestations of lower limb venous disease. Objective: To investigate the association between insufficient venous systems and the clinical classification of CEAP. Methods: A quantitative, cross-sectional, analytical, correlational design was carried out. Non-probability sampling for convenience. Sample size was 136 lower limbs from 71 patients. Chi-square, Monte Carlo and Odd ratio (OR) statistical tests were used with 95% confidence intervals through bivariate logistic regression (p<0.05). Results: 71.8% were female, average age of 66.1. The most frequent insufficient venous system was the superficial one (61.7%). 100% of the dilated great saphenous veins (GSV) had insufficiency. The most frequent CEAP clinical class was C2: 44.9%); 35.1% of C1 (telangiectasia) had an insufficient venous system and 50% of C2 had GSV insufficiency (p=0.227). There was an association between insufficiency of the superficial and deep venous systems and the CEAP clinical classification (p=<0.001). The deep venous system was associated with severe chronic venous disease of the lower limbs OR (6.04) with 95% CI (1.02-35.73) and p=0.047. Conclusions: An association was evident between the insufficiency of the superficial and deep venous systems with the clinical classification of CEAP. One third of lower limbs with C1 (telangiectasias) had an insufficient venous system.